Improving detection of corporate fraud in Singapore : insights from the press on the profile of fraud cases, fraudsters and whistleblowers. - Lee, Shan Shan. (2012)
Through content analysis of press coverage of 39 high-profile Singapore corporate fraud cases which took place between 2000 and 2011, this study sought to improve fraud detection in three ways.